Obturator Hernia – a Case Report - Paudel, Sharma; Suwal, Sundar; Kayastha, Prakash; Tuladhar, Sasmita (Journal of Karnali Academy of Health Sciences, 2022)
Background: An obturator hernia is a rare cause of an abdominal wall hernia. Obturator hernia as a cause of small bowel obstruction can be difficult to detect. Delayed diagnosis and treatment of this condition usually leads to a high mortality rate. Case Presentation: We present a case of an 82 year old lady who presented to the emergency with pain and abdominal distension of 3 days duration. Clinically, she had features of bowel obstruction. Ultrasonography revealed dilated small bowel loops. Contrast enhanced CT scan of the abdomen and pelvis was obtained which showed left obturator hernia with features of small bowel obstruction. The patient underwent emergency exploratory laparotomy which revealed left obturator hernia with ileal loop as content. Approximately 40 cm of non-viable distal ileum was resected and ileo-ileal anastomosis was performed. Post-operative period was uneventful. Conclusion: Obturator hernia, though rare is an important cause of intestinal obstruction. High index of clinical suspicion is needed especially in emaciated elderly women who presents with intermittent medial thigh pain and features of bowel obstruction. Immediate surgery is the life-saving procedure.